La Malinche: de la subrepresentación a la reivindicación. Malinche ayer, Marina hoy - María Rocío Ruiz Pleguezuelos (Les Cahiers ALHIM)
Many historical figures have been rejected, distorted or simply under-represented on the big screen and therefore on the small screen. This has been the case of many of the characters that were part of the history of the conquest of America by the Spanish, being Marina, known as La Malinche, one of the most ignored and mistreated by cinema. Her historical figure has suffered rejection and criticism for centuries and this negativity has also been transmitted to the audiovisual media; contaminating her figure that has appeared on few occasions and, almost always, in a fleeting way, and with little weight for the story developed in the film. The works of recent times seem to want to vindicate this woman who, in addition to being a slave, lover and mother, was an intelligent translator and a crucial element in the takeover of the Mexican empire by the Spanish.